2019
DOI: 10.21203/rs.2.12014/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quick selenium accumulation in the selenium-rich rice and its physiological responses in changing selenium environments

Abstract: Background:The element selenium (Se) deficiency is thought to be a global human health problem, which could disperse by daily-supplement from Se-rich food. Increasing the accumulation of Se in rice grain is an approach matched to these nutrient demands. Nonetheless, Se is shown to be essential but also toxic to plants, with a narrow margin between deficiency and toxicity. Notably, the regulatory mechanism balancing the accumulation and tolerance of Se in Se-rich rice plants remains unknown. Results:In this stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Rice is a staple food for residents in many areas of China, and its ability to accumulate Se is strong (18). Therefore, Se-rich rice is regarded as a good Se supplement (19). However, previous studies have shown that rice could easily absorb and accumulate heavy metals from soil (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is a staple food for residents in many areas of China, and its ability to accumulate Se is strong (18). Therefore, Se-rich rice is regarded as a good Se supplement (19). However, previous studies have shown that rice could easily absorb and accumulate heavy metals from soil (20,21).…”
Section: Introductionmentioning
confidence: 99%